The Diversity Of Weeds In Organic Linseed And Flax Crop (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The flax is grown in the world for many years. The area of linseed in the world is much more than that of fibre flax. The seeds of ecologically grown linseed have high value as the row material for food, medicine, fodder, oil production. The cold pressed oil and seeds of ecologically grown linseed are especially popular in EU, Canada and USA. The quality of the finished linen product is often dependent upon growing conditions and harvesting techniques. The organic textile trend is starting to develop worldwide, while in Lithuania it is still almost non-existent. Therefore, the chance for Lithuanian farmers appears to export the ecological seed and fiber, not only use them in local market. Lithuanian farmers are in luck for the advices how to grow flax in ecological way. Therefore, in 2007- 2009 some investigations were carried out at the Upytė Experimental Station of the Lithuanian Research Centre for Agriculture and Forestry (Panevėžys district, Lithuania). The results of our investigation showed that it is possible to grow and harvest fibre flax and linseed in organic farms without any pesticides. The incidence of weeds is one of the biggest problems in organic growing of flax and linseed.